Contributing factors to the choice of medical specialty in Brazil: An integrative review (Research, Society and Development, 2025)
Introduction: Choosing a medical specialty is a key step in physicians’ professional trajectories and has important implications for health workforce planning. In Brazil, this process takes place in a context of regional inequalities, structural challenges within the health system, and changes in medical students’ profiles. Objective: To evaluate the contributing factors to the choice of medical specialty in Brazil. Methods: An integrative literature review was conducted in April and May 2024 using the Virtual Health Library (VHL). DeCS/MeSH descriptors related to career choice, specialization, medical students, and Brazil were combined using the Boolean operator AND. Study selection followed the PRISMA 2020 guidelines, resulting in a final sample of 14 studies. Results: The findings indicate that medical specialty choice is influenced by multiple interrelated factors, including affinity with the specialty, personal satisfaction, lifestyle and quality of life, income expectations, professional prestige, clinical experiences during undergraduate training, extracurricular activities, family influence, and role models. Low interest in Family and Community Medicine was associated with perceptions of lower professional recognition. Conclusion: Medical specialty choice in Brazil is a complex process shaped by individual, academic, and institutional factors. Educational strategies and public policies aimed at improving professional valuation and training experiences are essential to promote a balanced medical workforce.